Tourist-Based Waste Management with Deposit Refund Implementation in Manggar Beach Area, Balikpapan Indonesia - Shella, All Free; Ekayani, Meti; Sapanli, Kastana (Journal La Lifesci, 2024)
The management of the Manggar Beach tourist area cannot be separated from obstacles related to the problem of waste generation. The problem of waste generation also results in the loss of aesthetic value and beauty of the beach, which decrease tourist interest in the tourism area. Therefore, efforts are needed to maintain the sustainability of the tourist environment by building tourist participation related to tourism waste management by applying the concept of the polluter pays principle so that tourist area more responsible for the waste they produce. Travel-based waste management can be done with a refund deposit mechanism. This study aims to (1) identify waste generation and the composition of the types of waste produced by tourists in the Manggar Beach tourist area; (2) analyze tourist perceptions regarding tourist-based waste management in the Manggar Beach tourist area; (3) measure the value of tourists' willingness to pay (WTP) on the amount of deposit refund in waste management in the Manggar beach tourist area. The result showed that plastic is the largest waste generation by tourist and 93% of tourists are willing to implement DRS for their waste. Thus, deposit refunds based on tourist’ WTP can cover operational costs for waste management in the Manggar Beach Area, so that DRS can be implemented in the Manggar Beach Area.